Systematic analysis of the global, regional, and national burden of subarachnoid hemorrhage from 1990 to 2021 - Wanyue Li; Huafei Yang; Furong Rui; Xinyi Ruan; Jun Xiong; Lin Chen (PLoS ONE, 2025)
Subarachnoid hemorrhage (SAH) is characterized by high rates of morbidity, mortality, and disability, which imposes a heavy disease burden on society and families. Incidence, mortality, disability-adjusted life years (DALYs) and their corresponding age-standardized rates (ASRs) and estimated annual percentage changes (EAPCs) of subarachnoid hemorrhage were analyzed by using GBD 2021 data in our study. Data were further stratified by age, sex, and region. Globally, in 2021, there were 697486 (95% UI, 614334795785) new cases of subarachnoid hemorrhage, 352,810 (309015401474) deaths, and 10.64 million (9.39 to 12.12) DALYs. The burden of subarachnoid hemorrhage showed substantial decline from 1990 to 2021. However, the decline in the age-standardized incidence rate was significantly smaller than the declines in the age-standardized mortality rate and age-standardized DALY rate, with the most pronounced downward trend in East Asia but an increase in sub-Saharan Africa, indicating that our prevention strategies require further refinement.